Repurposing of Four Drugs as Anti-SARS-CoV-2 Agents and Their Interactions with Protein Targets - Luis C. Vesga; Camilo A. Ruiz-Hernández; Jeimmy J. Alvarez-Jacome; Jonny E. Duque; Bladimiro Rincon-Orozco; Stelia C. Mendez-Sanchez (Scientia Pharmaceutica, 2022)
Although there are existing vaccines against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), new COVID-19 cases are increasing due to low immunization coverage and the emergence of new variants. For this reason, new drugs to treat and prevent severe COVID-19 are needed. Here, we provide four different FDA-approved drugs against SARS-CoV-2 proteins involved in the entry and replication process, aiming to identify potential drugs to treat COVID-19. We use the main protease (Mpro), the spike glycoprotein (S protein), and RNA-dependent RNA polymerase (RdRp) as protein targets for anti- SARS-CoV-2 drugs. In our constructed database, we selected different drugs against each target (Mpro, S protein, and RdRp) based on their common interactions with relevant residues involved in viral entry at the host cell and replication. Furthermore, their stability inside the binding pocket, as well as their predicted binding-free energy, allow us to provide new insight into the possible drug repurposing of viomycin (interacting with Mpro) due to its interactions with key residues, such as Asn 143, Glu 166, and Gln 189 at the same time as hesperidin (interacting with the S protein) is interacting with residues Tyr 449, Ser 494, and Thr 500, keeping inside the predicted binding pocket, as well as interacting with residues in different variants of concern. Finally, we also suggest nystatin and elvitegravir (interacting with RdRp) as possible drugs due to their stability within the predicted pocket along the simulation and their interaction with key residues, such as Asp 760, Asp 761, and Asp 618. Altogether our results provide new knowledge about the possible mechanism of the inhibition of viomycin, hesperidin, elvitegravir, and nystatin to inhibit the viral life cycle of SARS-CoV-2 and some of its variants of concern (VOC). Additionally, some iodide-based contrast agents were also found to bind the S protein strongly, i.e., iohexol (−58.99 Kcal/mol), iotrolan (−76.19 Kcal/mol), and ioxilan (−62.37 Kcal/mol). Despite the information we report here as the possible strong interaction between these contrast agents and the SARS-CoV-2′s S protein, Mpro, and RdRp, we believe that further investigation, including chemical modifications in their structures, are needed for COVID-19 treatment.